The nutrient supply of pathogenic fungi; a fertile field for study - Solomon, P.; Tan, Kar-Chun; Oliver, Richard (2003)
Phytopathogenic fungi must feed on their hosts to propagate and cause disease. Their ability to access the rich nutrient supply offered by living plants is one of the most obvious properties that distinguish pathogens from saprophytes. Successful invasion by pathogens depends as much on their ability to utilize the available nutrient sources offered by plants as on their ability to penetrate plants and evade defensive mechanisms. Here, we review current knowledge on the nature of the nutrient supplies utilized by pathogens during infection.The available evidence is rudimentary in most cases. There is much evidence to suggest that fungal metabolism can be divided into at least two phases. The first is based on lipolysis and occurs during germination and penetration of the host. The second phase uses glycolysis and predominates during the invasion of host tissue. We also propose, mainly on theoretical grounds, that a third phase of nutrition occurs late in infection during which new spores are produced.Contrary to early assumptions, the nitrogen sources available to some pathogens appear to be abundant. The idea that nitrogen starvation is a cue that controls fungal gene expression during infection may need to be reassessed. Very little is known about the micronutrient (Fe, S, P) or vitamin supply. The knowledge gained from this research may enable the design of new antifungal strategies targeting potential weaknesses in fungal metabolism and will also impact on agronomic practices.